Detection and selection of dye-degrading bacteria from surface waters with different degrees of contamination - Grifes Paisan, Luciana (2025)
Biodegradability and resistance from indigenous bacterial communities to dyes were tested using samples from both polluted and unpolluted surface waters in Buenos Aires. Five dyes were selected for the study: Acid Black 210, Direct Orange 39, Malachite Green, Gentian Violet, and Alizarin Red. Water quality was assessed by measuring chemical oxygen demand, biochemical oxygen demand, and both Escherichia coli and enterococci counts. Biodegradability was tested using a respirometric method, while resistance was assessed by determining the minimum inhibitory concentration (MIC). No bacterial strains capable of degrading the dyes as the sole carbon source were isolated from the respirometric tests. However, from the MIC tests, 28 strains capable of dye discolouration were identified, using nutrient broth as a supplement. Two of them were able to degrade Malachite Green and Acid Black 210 at a concentration of 50 mg L 1 in less than 24 h and with an efficiency greater than 87%. These strains were identified as Aeromonas sp. and Shewanella sp. through MALDI-TOF/MS and 16S rRNA gene sequencing. The determination of biodegradability and resistance can be used to enhance the characterization of watercourses. Furthermore, this methodology provides a means to isolate biodegrading bacteria that could be applied in effluent treatment processes.